Design of adaptive analog filters for magnetic front-end read channels - Garrido, N. (2015)
This thesis studies the design and behavior of continuous-time very-high-frequency filters. The motivation of this work was the search for filtering solutions for the read- channel in recording and reproduction of data on magnetic media systems, with costs and consumption (total size less than 1 mm2 and consumption under 1mW/pole), lower than the available circuits. Accordingly, as was done in this work, the rapid development of microelectronics technology raised very significant efforts worldwide in order to investi- gate new techniques for implementing such filters in monolithic integrated circuit, espe- cially in CMOS technology (Complementary Metal Oxide Semiconductor). We present a comparative study on different hierarchical levels of the project, which led to the reali- zation and characterization of solutions with the desired characteristics. In the first level, this study addresses the conceptual question of recording and transmission of signal and the choice of good mathematical models for the processing of information and minimization of error inherent in the approaches and in accordance with the principles of the characterized physical devices. The main work of this thesis is focused on the hierarchical levels of the architecture of the read channel and the integrated circuit implementation of its main block - the fil- tering block. At the architecture level of the read channel this work presents a compre- hensive study on existing methodologies of adaptation and signal recovery of data on magnetic media. This project appears in the sequence of the proposed solution for a low- cost, low consumption, low voltage, low complexity, using CMOS digital technology for the performance of a DFE (Decision Feedback Equalization) based on the equalization of the signal using integrated analog filters in continuous time. At the project level of implementation of the filtering block and techniques for im- plementing filters and its building components, it was concluded that the technique based on transconductance circuits and capacitors, also known as gm-C filters is the most ap- propriate for the implementation of very-high-frequency adaptive filters. We defined in this lower level, two sub-levels of depth study for this thesis, namely: research and anal- ysis of optimal structures for the design of state-space filters, and the study of techniques xi for the design of transconductance cells in digital CMOS circuits for the implementation of continuous time integrated analog filters. Following this study, we present and compare two filtering structures operating in the space of states, corresponding to two alternatives for achieving a realization of an adaptive equalizer by the use of a continuous-time third order allpass filter, as part of a read-channel for magnetic media devices. As a constituent part of these filters, we present a technique for the realization of transconductance circuits and for the implementation of linear capacitors using arrays of MOSFET transistors for signal processing in very-high-frequency integrated circuits us- ing sub-micrometric CMOS technology. We present methods capable of automatic ad- justment and compensation for deviation errors in respect to the nominal values of the components inherent to the tolerances of the fabrication process, for which we present the simulation and experimental measurement results obtained. Also as a result of this study, is the presentation of a circuit that provides a solution for the control of the head positioning on recording/playback systems of data on magnetic media. The proposed block is an adaptive first-order filter, based on the same transcon- ductance circuits and equalization techniques proposed and used in the implementation of the adaptive filter for the equalization of the read channel. This filter was designed and included in an integrated circuit (Jaguar) used to con- trol the positioning of the read-head done for ATMEL company in Colorado Springs, and part of a commercial product used in removable hard drives fabricated in partnership with a Scottish company.